Failure Patterns of Recurrence and Metastasis After Intensity-Modulated Radiotherapy in Patients With Nasopharyngeal Carcinoma: Results of a Multicentric Clinical Study - Chen, Sixia; Yang, Dong; Liao, Xueyin; Lu, Ying; Yu, Bin; Xu, Meng; Bin, Ying; Zhou, Pingting; Yang, Zhendong; Liu, Kang; Wang, Rensheng; Zhao, Tingting; et al. (Frontiers in Oncology, 2022)
ABSTRACT Purpose: This study aimed to explore factors associated with recurrence and metastasis after intensity-modulated radiotherapy (IMRT) in patients with nasopharyngeal carcinoma (NPC), and to provide evidence for the design of new NPC treatment strategies. Methods: We performed a retrospective analysis of 645 patients with NPC at three treatment centers in the Guangxi Zhuang Autonomous Region, China, between January 2009 and December 2012. Results: 9.3% of patients (60/645) had recurrence and 17.5% (113/645) had distant metastasis 5 years after treatment. The 1-year, 3-year and 5-year local recurrence rates were 0.9%, 6.5% and 9.0% and distant metastasis rates were 3.4%, 10% and 17.2%, respectively. In the 60 patients with recurrence, the in-field, marginal-field, and out-field recurrence rates were 93.3% (56/60), 5.0% (3/60) and 1.7% (1/60), respectively. Recurrence failures occurring within the first three years after treatment accounted for 81.7% (49/60). In the 113 patients with metastasis, the size of the cervical lymph node, the presence of lower cervical lymph node metastasis, the residual cervical lymph node size and the time of residual cervical lymph node complete response (CR) were independent prognostic factors for DMFS (P <0.05). Conclusion: Most recurrences happen in the first three years after IMRT. In-field recurrences are the most common pattern for loco-regional failure of NPC treatment. The risk of distant metastasis after IMRT is positively correlated with N staging, lower cervical lymph node metastasis, the size of the cervical lymph nodes, residual NPC in the cervical lymph nodes. Therefore more effective interventions should be explored.